Physics in your life - Richard Wolfson; Leven, Jon.; Reay, Alisha; The Great Courses (Chantilly, [Va.] : Teaching Company, 2004)
In this course of 36 lectures, Professor Richard Wolfson explores the physics of everyday events, commonplace technologies and natural phenomena, using an array of experiments, gadgets, props, computer animations, short videos, diagrams and pictures.
Keywords: Physics